Contemporary Consumer Health Informatics - Wickramasinghe, Nilmini; Troshani, Indrit; Tan, Joseph (Healthcare Delivery in the Information Age, 2016)
This innovative reference examines how consumer health informatics (CHI) can transform healthcare systems stressed by staffing shortages and budget constraints and challenged by patients taking a more active role in their care. It situates CHI as vital to upgrading healthcare service delivery, detailing the relationship between health information technologies and quality healthcare, and outlining what stakeholders need to learn for health IT systems to function effectively. Wide-ranging content identifies critical issues and answers key questions at the consumer, practitioner, administration, and staff levels, using examples from diverse conditions, countries, technologies, and specialties. In this framework, the benefits of CHI are seen across service domains, from individual patients and consumers to healthcare systems and global health entities. Included in the coverage: Use of video technology in an aged care environment- A context-aware remote health monitoring service for improved patient care- Accessibility issues in interoperable sharing of electronic health records: physician's perspective- Managing gestational diabetes with mobile web-based reporting of glucose readings- An organizing vision perspective for developing and adopting e-health solutions- An ontology of consumer health informatics- Contemporary Consumer Health Informatics combines blueprint and idea book for public health and health informatics students, healthcare professionals, physicians, medical administrators, managers, and IT practitioners.